Pendampingan Ekonomi Kreatif dalam Pemberdayaan Kerajinan Ecobrick Ditinjau dari Perspektif Ekonomi Islam - Maulida, Siti Alifia; Kahfi, Kahfi (Neolectura, 2023)
Garbage that accumulates will cause a lot of losses for us, therefore we need Waste Management. If we are able to manage waste properly, we will get a positive impact on the environment and also benefits in the economic aspect. To overcome the problem of waste, it is necessary to make changes that view waste as a resource that has economic value and can be utilized. Which was originally just throwing garbage frivolity place changed to waste management by applying 3R (Reduce, Reuse, Recycle). One of the efforts in waste management in a good and right way is to use the Ecobricks concept which is able to reduce the amount of plastic waste that is difficult to decompose. The aim of writing this scientific work is to find out the causes of the accumulation of waste and to find solutions to the accumulation of waste in Banyuwangi Village. This research was conducted using qualitative research. This is because qualitative research methodology is a scientific research that aims to understand a phenomenon in a natural social context by prioritizing the process of in-depth communication interaction between the researcher and the phenomenon under study. One of the goals of Ecobricksing is to change habits that have not previously been a special concern in maintaining environmental cleanliness. This can be used as an opportunity and make it an alternative solution for the people of banyuwangi village in developing and improving knowledge about plastic waste management and the creativity of local residents in utilizing materials that exist in the surrounding environment that have a positive value in the lives of residents, such as utilizing plastic waste to make it a valuable product.